Acculturation, acculturative stress and resilience among older immigrants in United States. (20th May 2019) - Serafica, R.; Lekhak, N.; Bhatta, T.
Abstract : Background: Previous studies have demonstrated a strong and consistent association between higher acculturative stress and poorer mental and physical health outcomes while acculturating to a new country. Acculturative stress is multifactorial and nurses work in variety of settings that encounter older immigrants with different levels of acculturative stress. Research on resilience among older immigrants has linked resilience to successful acculturation. Purpose: The aim of this study was to explore the interplay between acculturation, acculturative stress and resilience, and their collective impact on physical and mental health self‐evaluation among older Filipino Americans. Method: This study employed a cross‐sectional, quantitative, descriptive design using older Filipino immigrants, 55 years and older ( N = 123) who were living in the western part of the United States. Findings: Our study found that the levels of acculturation did not have a significant influence on self‐evaluation of physical and mental health; however, acculturative stress and resilience had an indirect effect on physical and mental health. Conclusions: This study reemphasized the importance of assessing the acculturative stress and determining resiliency among older immigrants who might be undergoing acculturation‐based conflicts with their families and community. Promoting a low level of acculturative stress and high resilience is key to shaping interventions to obtain better health outcomes among this population. Implications for nursing policy: Nurses can support and augment the efforts of professional nursing organizations to advocate and encourage legislation and policy to improve the physical and mental well‐being of older immigrants. Policymakers should focus on additional resources for older adults from other countries to reduce their stress or enhance their resilience.